Attention passengers : your flight has been delayed! - Kulkarni, Vaibhavi, (SAGE Knowledge. Cases., 2017)
The case describes a customer-care crisis scenario, which occurs when a Newark to Ahmedabad flight (via Mumbai) is severely delayed. After the airplane begins taxiing, a series of technical snags occur, causing a five-hour delay. Consequently, the flight which was expected to take off from Mumbai at 6 p.m., departed at 11 p.m.The captain, Shubhendu Chatterjee, attempts to manage the situation through a series of announcements providing the passengers with updates regarding the situation. During the course of the five hour delay, reactions from the passengers on board are mixed, with some irate passengers demanding that they be allowed to disembark and others, resigned to the delay. Students are invited to consider what they would have done differently in this scenario and how best to deal with a customer-care crisis.